IgG4‐Related Prostatitis Impairs Objective Urinary Function as with Benign Prostate Hyperplasia: A Case Report Successfully Treated with Transurethral Resection. Issue 3 (29th April 2014) - KAGAWA, Makoto; TAKESHITA, Hideki; MORIYAMA, Shingo; ADACHI, Akiko; CHIBA, Koji; NORO, Akira
<x xml:space="preserve">Abstract</x> Case We report a case of IgG4‐related prostatitis successfully treated with transurethral resection of the prostate (TUR‐P). A 47‐year‐old man with a history of autoimmune pancreatitis and sclerosing cholangitis presented with lower urinary tract symptoms. Because ultrasonography revealed a mildly enlarged prostate and uroflowmetry showed a severely diminished flow curve, benign prostatic hyperplasia was diagnosed. Despite the administration of α1‐blockers, the patient's condition did not improve, and TUR‐P was performed in accordance with his wish. Outcome Pathological examination showed dense lymphoplasmacytic inflammation with no evidence of synchronous malignancy. On immunohistochemical staining, a large number (>40/high‐power field) of IgG4‐positive cells were observed in the lesions showing the inflammation, confirming the diagnosis of IgG4‐related prostatitis. The patient's urinary function dramatically improved postoperatively, and good urinary function has been maintained for 3 years without additional treatment. Conclusion Recognition of the impact of IgG4‐related prostatitis on objective urinary function will help in appropriately treating patients with this condition.